Effectiveness of LMS-based digital learning methods on improving Indonesian language literacy among students of SMP Muhammadiyah Rappang - Idayanti Idayanti; Abd Kahar; Isumarni Isumarni; Muhammad Hanafi; Sam Hermansyah; Usman M (Edumaspul: Jurnal Pendidikan, 2025)
This study examines the effectiveness of a digital learning method based on a Learning Management System (LMS) in improving Indonesian language literacy among students at SMP Muhammadiyah Rappang. The research is grounded in the increasing need for technology-enhanced learning that supports literacy development in the digital era. A quantitative approach with a quasi-experimental pretest–posttest control group design was employed. The sample consisted of two classes: an experimental group that received instruction through the LMS and a control group taught using conventional methods. Data were collected through validated reading and writing literacy tests and analyzed using a t-test to determine significant differences between groups. The findings indicate that students in the LMS-based class showed higher gains in literacy skills compared to those in the traditional class. Key LMS features—structured materials, multimedia resources, discussion forums, and automated assessment—contributed to increased motivation, independent learning, and text comprehension. These results demonstrate that LMS-based digital learning is effective in enhancing literacy competencies among junior high school students. The study recommends the continuous integration of LMS platforms and the development of more diverse digital learning content for Indonesian language instruction.